Numerical study of air compressibility effects in breaking wave impacts using a CIP-based model. (15th February 2019) - Sun, Hongyue; Sun, Zhaochen; Liang, Shuxiu; Zhao, Xizeng
Abatract: The prediction of breaking wave loads is challenging in ocean engineering due to air entrapment and compressibility. In order to investigate air compressibility effects in different modes of breaking wave impact, a two-phase compressible flow model is proposed. A high-order finite difference method, Constrained Interpolation Profile (CIP) method is employed to discretize the Navier-Stokes equations, and the interface is captured by Tangent of Hyperbola for Interface Capturing (THINC) scheme. The present compressible model is validated against several tests: 1-D gravity-induced liquid piston motion, idealized free drop of water patch impact and dam-break experiments. Special attention of this study is paid to breaking wave impacts on a vertical wall in a liquid sloshing tank. For air entrapped impact, the results of CIP-based compressible model are in good agreement with experimental data. It is shown that the air compressibility leads to high-frequency oscillation of the impact pressure, which cannot be reproduced by the incompressible model. It is found that the oscillation of the impact pressure is synchronized with the compression and expansion of the entrapped air pocket, and the oscillation frequency is related to the size of air pocket. For air-water mixing impact, the oscillation of the pressure may be more intense.